(untitled) (Bangladesh Journal of Animal Science, 2013)
A total of 68 Bhutanese indigenous chicken eggs were collected from Research station (imitating improved management) and villages (farmers management) to estimate the egg quality. The weight of eggs sampled from Research farm was comparatively heavier (50.63g ± 5.04) than the extensive farmers system (45.94 ± 5.68). The yolk index was higher (39.85%±5.69) in village management than that of improved management (41.93% ±